STUDI BISNIS MODEL CANVAS DALAM PENGEMBANGAN USAHA DAN WIRAUSAHA MUDA DI DENPASAR - Putu Selviani; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Berdikari, 2022)
Through a business feasibility study, business owners can find out whether Goldmine Coffee is feasible to run. The study used quantitative and qualitative data analysis techniques, data obtained through interviews and documentation conducted at Goldmine Coffee Sanur. The feasibility analysis uses non-financial aspect analysis by analyzing market and marketing aspects. To find out the business opportunities for Goldmine Coffee, a SWOT analysis. While the analytical tools used for the feasibility of analyzing the financial aspect use the analysis of Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period (PP). The results showed that Goldmine Coffee is in quadrand IV position with a strong competitive position. Based on the results of the analysis of the financial aspect, the positive Net Present Value (NPV) was Rp. 791,313,749, the Internal Rate of Return (IRR) is 70%, the Profitability Index (PI) is greater than 1, which is 7.5%, with the Payback Period (PP) of this business for 4 months 25 days. For the business model of Goldmine Coffee, which is a player in the beverage industry, it is said to be strategic in an industry. Thus Goldmine Coffee is said to be worth running.